Biologia- Programma Nazionale di Ricerche in Antartide - S. FOCARDI; R. BARGAGLI; G. di PRISCO; V. LIBERA; S. MOTTA; M. NIGRO; S. SEDMAK; PISANO, EVA (1991)
Rapporto di spedizione Esate Australe 1990/91, ENEA, Roma: 31-57